PROFIL MEDIA PEMBELAJARAN BERBASIS WEB UNTUK MELATIH KEMANDIRIAN BELAJAR PADA MATERI VIRUS - Susilowati, Purwo (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
This research aims to produce thirth draft of web-based learning media on the virus matter which theoretically suitable appropriate for train self directed learning. The research designed by ASSURE model. Making web-based learning media use dot.tk domain and WordPress application service. The developed student worksheet was tested on 15 students in 10th grade of SMAN I5 Surabaya. The instrument that is being used is suitability sheet. This research results a web-based learning media that suitable for use as a learning media based on content component, language component and presenting component. Keywords: web-based learning media, self directed learning, ASSURE, virus